2021
DOI: 10.4236/ijcm.2021.123011
|View full text |Cite
|
Sign up to set email alerts
|

Current Problems of Diagnostics and Treatment of Purulent-Inflammatory Diseases and Sepsis in Medical Practice

Abstract: Background: Poor treatment of burns can lead to sepsis and even death. Especially promising is the use of the method of fluorescence spectroscopy for its diagnostics. The aim of the research is to create a pathogenetic concept as the basis of a diagnostic and treatment model of purulent-inflammatory diseases and sepsis. Material and methods: The study lasted from 2001 to 2019 and included 4 stages. The experimental base of luminescent research at all stages was the luminescence laboratory of the Department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…During the pandemic of COVID-19, there were difficulties in using MFS in the treatment process, in particular for patients with burn injury. The analysis of the obtained results of the treatment of patients with burn disease [16] with the use of MFS helped to treat successfully over 35 patients with burn injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic of COVID-19, there were difficulties in using MFS in the treatment process, in particular for patients with burn injury. The analysis of the obtained results of the treatment of patients with burn disease [16] with the use of MFS helped to treat successfully over 35 patients with burn injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 4 presents the results of research in the dynamics of fluorescence spectra, and Table 6 shows data for the spectral-fluorescent characteristics of the BS of the patient with the burn injury (area of the burn surface 38%), who was admitted to the hospital on 27 June 2015 [16]. He was immediately prescribed appropriate treatment, including antibiotic therapy and infusion therapy with 2-3 liters daily.…”
mentioning
confidence: 99%
“…Purulent-Inflammatory Diseases and Sepsis Over the past twenty years, some authors [10] [11] have demonstrated the diag-nostic value of MFS, which was illustrated specifically on the disease models "in vitro" [12], as well as specifically "in vivo" and confirmed in clinical practice for patients with obstetric [13] and surgical [14] pathologies and with burn injury [15] [16]. Considerable attention was paid to the understanding of the essence of the pathological processes that occur in the bodies of patients with purulentseptic diseases at the molecular level.…”
Section: The Modified Diagnostic and Treatment Model Ofmentioning
confidence: 99%
“…If Х is more than Х*, this ensures the viability of the organism to some extent. The in-depth analysis of the obtained experimental results for the spectral-fluorescence characteristics of the BS of patients with sepsis [8,10] and with burn injury [11,12] based on the proposed concept made it possible to understand properly the main features of their behavior during the progression of the disease, including when approaching septic condition, as well as in the process of recovery. The main characteristics which we investigate within the MFS for the BS of patients with purulent-septic complications are I F and (λ max ).…”
Section: Scientific Trends and Trends In The Context Of Globalization...mentioning
confidence: 99%